Code Shift in the Digital Communication of Generation Z in Indonesia - Azmi, M Ulul; Fatimah, Ayu Bakti; Khomisah, Khomisah; Salsabila, Ghelsa Nashwa (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study investigates the phenomenon of code shift in the digital communication of Generation Z in Indonesia. Having grown up in a digital environment, Gen Z exhibits linguistic patterns that are unique, flexible, and adaptive to the rapid development of information technology. Using a descriptive qualitative approach, the research examines various forms of digital communication on social media and instant messaging applications. The findings indicate lexical, grammatical, and syntactic shifts marked by the use of slang, digital acronyms, code-mixing, and code-switching within a single discourse. Contributing factors include technological, social, cultural, psychological, and algorithmic forces that foster distinct language styles within digital communities. The implications include challenges in upholding standard Indonesian in formal domains, intergenerational communication gaps, and the need for more contextually relevant language education policies. The study aims to deepen our understanding of linguistic dynamics in the digital age and to inform language policy strategies that are adaptive to contemporary conditions.